Enzymatic Synthesis of Glycosphingolipids: A Review - Li, Qingjiang; Guo, Zhongwu (Synthesis, 2021)
Glycosphingolipids (GSLs) are the major vertebrate glycolipids, which contain two distinctive moieties, a glycan and a ceramide, stitched together by a β-glycosidic linkage. The hydrophobic lipid chains of ceramide can insert into the cell membrane to form ‘lipid rafts’ and anchor the hydrophilic glycan onto the cell surface to generate microdomains and function as signaling molecules. GSLs mediate signal transduction, cell interactions, and many other biological activities, and are also related to many diseases. To meet the need of biological studies, chemists have developed various synthetic methodologies to access GSLs. Among them, the application of enzymes to GSL synthesis has witnessed significant advancements in the past decades. This short review briefly summarizes the history and progress of enzymatic GSL synthesis.1 Introduction1.1 The Glycosphingolipid Structure1.2 GSL Biosynthesis1.3 Functions and Biological Significance1.4 Overview of GSL Synthesis1.5 Scope of the Review2 Glycotransferases for GSL Synthesis3 Glycosynthases for GSL Synthesis4 Enzymatic Synthesis of Ceramide5 Conclusion
Keywords: glycosphingolipid; carbohydrate; ceramide; enzymatic synthesis; glycosyltransferase; glycosynthase